Intelligent Key (IKey) The key of Securing Cars - Sultan Saad Alshamrani; Abdulaziz Othman; Ahmed Saad; Salem Alaidaros; Feras Abo Alaoun; Mohammed Sadiq; Ramiz Farouq (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2020)
With the advancement of technology, applications have become an indispensable part of daily life to solve many problems. Technology is one of the important contents that promotes communication between people and enhances the acquisition and acquisition of information. Therefore, the development of information technology is the reason for the major scientific and knowledge revolution, which has an impact on the convenience of human life in various scientific journals. To recognize our responsibility, we came up with the idea of replacing physical objects with applications that increase usability in our life. As we strive to develop a smart car control application, the application can save the driver from the car key. Therefore, the application controls certain functions in the car, such as opening and closing doors and starting and stopping the engine. By connecting the app to the car and ensuring that the user does not need to carry the car key. As a result, now we are able to provide convenience and luxury to our customers and end-users.